The people vs. the power bloc? Popular music and populism. Issue 3 (October 2022) - Dunkel, Mario; Schiller, Melanie
Abstract : On 12 November 2017, the Philippine celebrity musician Pilita Corrales was singing the popular song 'Ikaw' ('You') at a gala event in Manila, attended by some of the world's most powerful politicians at the time, US President Donald Trump and Philippine President Rodrigo Duterte. Suddenly, she noticed a male voice singing along with her, its intonation off, its volume increasing. Aware that the event was being recorded, Corrales at first tried to disregard the intruding voice. Eventually however, she could no longer ignore it and, shielding her eyes from the lights with one hand, she tried to spot the uninvited singer in the audience. 'Where are you, sir'? she asked. Realising that the singer was on one of the balconies, it dawned on her that he was none other than Duterte himself. After giving Duterte room to sing a section by himself, she then joined the president in the song's finale (BBC News 2017 ; Guardian News 2017 ; Rappler 2017 ).